Defect levels in SnS thin films prepared using chemical spray pyrolysis - Kartha, C. Sudha. (2013)
The origin of various defect levels in the SnS thin films deposited using chemical spray pyrolysis (CSP) technique has been explored in this manuscript, by employing low-temperature photoluminescence (PL) technique. Concentration of Sn in the samples was varied purposefully by ex situ diffusion in order to alter the defect levels. The acceptor level obtained at 0.22 eV from the Arrhenius plot, has been assigned as the defect level caused by the Sn vacancies present in the lattice. Two shallow donor levels are conclusively identified and their activation energies have been estimated. The present study could also unearth a trap level in the forbidden energy gap which was due to the oxygen contaminant occupied by the vacancy of Sn. This trap level could be removed by annealing the sample in vacuum or through the ex situ diffusion of Sn. Employing Kelvin probe force microscopy (KPFM), the work-function of SnS was obtained as 4.925 eV, from which the position of the Fermi level could be assigned. Based on the present work, an energy level scheme for SnS thin films is proposed outlying origin of various defect levels.